METODE FORWARD CHAINING UNTUK DIAGNOSA PENYAKIT DAN HAMA PADA TANAMAN KOPI - Joko Kuswanto; Dwi Leosan Daya, Dhavid; Herdiansyah, (Journal of Computer Science and Technology (JCS-TECH), 2025)
Various problems can be encountered in agriculture, for example problems about diseases and pests in coffee plants. There are few experts or experts in the field of agriculture, so it is necessary to build a system that is able to adopt human processes and ways of thinking in the form of an expert system. The purpose of this study is to build an expert system to diagnose diseases and pests in coffee plants. The method used in this study is the forward chaining method. The system testing was carried out using the black box testing method which was tested on experts and coffee farmers. Based on the test results, the results of the assessment were obtained that the expert system for diagnosing diseases in coffee plants that was built was proven to work well as expected with 100% validation. Based on the results of the research that has been carried out, it can be concluded that the application that has been built is another alternative for users, both the general public or people who are having problems with diseases in coffee, which can be used as a guide as a step to seek control of the diseases experienced